2012
DOI: 10.4194/1303-2712-v12_3_15
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study wasto determine the optimal dose and the time required to reach a stable level of anaesthesia using clove oil and benzocaine on Siberian sturgeon fry (Acipenser baerii Brandt, 1869) with a mean length of 10.0±0.93 (7.2-12.0) cm and weight of 4.1±0.95 (2.1-6.4) g, and to compare the effects of them on feed intake after anaesthesia. In addition, the survival time and relationship between exposure duration and recovery time in 96 min with the optimal concentrations of these two anaesthetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 40 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, for Siberian sturgeon juveniles, substantially lower concentrations of clove oil (60 to 90 mg/L) were proposed as an appropriate dose range to minimize stress responses [38]. Another previous study on Siberian sturgeon fingerlings has indicated that the effective concentration of clove oil should be 330–381 mg/L [39]. However, in contrast to previous studies, our findings suggest that clove oil is not a suitable anesthetic for Siberian sturgeon prolarvae, due to prolonged recovery times (>8 min to >26 min with test doses 50 to 400 mg/L).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, for Siberian sturgeon juveniles, substantially lower concentrations of clove oil (60 to 90 mg/L) were proposed as an appropriate dose range to minimize stress responses [38]. Another previous study on Siberian sturgeon fingerlings has indicated that the effective concentration of clove oil should be 330–381 mg/L [39]. However, in contrast to previous studies, our findings suggest that clove oil is not a suitable anesthetic for Siberian sturgeon prolarvae, due to prolonged recovery times (>8 min to >26 min with test doses 50 to 400 mg/L).…”
Section: Discussionmentioning
confidence: 99%